STUDENTS AWARENESS ON THE REGULATION OF INTELECTUAL PATENT RIGHTS ON THEIR WRITTING PRODUCTS (a case study on the students of State Polytechnic of Madiun) - indrasari, febrina; Setiyawan, Agustinus Doedyk (Muhammadiyah University Press, 2018)
Students as an intellectual group should be able to be pattern for the younger generation, for example to behave honestly and responsibly. In the making of writing products, students must have an honest attitude in making writing products. To create students honest behavior cannot be separated from the role of the institution to form a culture of honest behavior by not doing plagiarism against the work of others. This is the reason of the author to make a study with the title Students Awareness on the Regulation of Intelectual Patent Rights on Their Writting Products (A Case Study on the Students of State Polytechnic of Madiun)Based on the principal issues stated above, the purpose of this legal research are:To know whether or not the students of State Polytechnic of Madiun have an awareness on the regulation of Intelectual Patent Rights On Scientific WritingTo determine what factors influence the level of regulation awareness of students State Polytechnic of Madiun to Copyright on Scientific WritingResearch method used in this research is empirical sociological approach method that have intention to observe how is the reaction and interaction happened when system norm (law) work in the society that is to know whether the students of State Polytechnic of Madiun already have an awareness of law to Â the Intellectual Patent Right of Scientific Writing and to know what factors may give influence to their level of law awareness of copyright on Scientific WritingBased on the above discussion about students legal awareness of intellectual property rights of copyrights on paper case study of Polytechnic State student of Madiun, it can be concluded that the students legal awareness of copyright rights of writing is still low, indicated by the number of students who know about knowledge IPR / Copyright is still small. The copyright infringement is still committed, i.e., taking photocopies of ordinary and reasonable regardless of the sanctions or rules, then in the case of quoting other peoples scientific papers or books, the awareness to include the source of the quotation is still low.Regarding the factors behind the level of law awareness of the students of State Polytechnic of Madiun on the copyright of the paper, the first factor of knowledge and understanding of law, as a whole the students have a low level of knowledge and legal understanding, can be seen from the two aspects contained in it that is about knowledge rules or laws governing and their aims and objectives. Many respondents who only know one of them, know the rules governing, but do not know the purpose of the rule, vice versa. The second concerning legal attitude and legal behavior, most of the students legal attitude is good, but still many are not good, due to cultural habit factor in the environment and influenced by friends around.